Opportunistic Routing using Wireless Sensor Networks - Prankur Gupta; Amar R.; Dr. H.C. Srinivasaiah (Journal of Electronic Design Engineering, 2019)
Wireless Sensor Networks (WSN) are used in our daily life for monitoring and controlling application because of it’s unique features such as low power consumption, reduced cost, and implementation with ease. To improve the lifetime of wireless sensor networks energy efficient routing protocol is very necessary to choose in the network layer of WSN. A comparative analysis based on performance and energy consumption referring to opportunistic routing algorithm is done. It is being evaluated in terms of energy consumed, packets lost, flow rate and throughput. We see that Opportunistic routing algorithm performs way better than the entire traditional routing algorithm. The results provided show that Opportunistic routing give significant improvement in power consumption.